2019
DOI: 10.1371/journal.pone.0217624
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G structure and rheumatoid factor epitopes

Abstract: Antibodies are important for immunity and exist in several classes (IgM, IgD, IgA, IgG, IgE). They are composed of symmetric dimeric molecules with two antigen binding regions (Fab) and a constant part (Fc), usually depicted as Y-shaped molecules. Rheumatoid factors found in patients with rheumatoid arthritis are autoantibodies binding to IgG and paradoxically appear to circulate in blood alongside with their antigen (IgG) without reacting with it. Here, it is shown that rheumatoid factors do not react with na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 55 publications
2
29
0
4
Order By: Relevance
“…In the presence of residual moisture, freeze‐dried proteins can undergo disulfide interchange and other reactions 13 . Therefore, the data we obtained on the specificity of RF detected in the blood of rheumatoid arthritis patients are consistent with the data that the pathological RF is specific to epitopes that are hidden in the IgG structure (cryptic epitopes) and only become exposed by conformational changes, which may occur upon antigen binding in vivo or in vitro, upon immobilization on surfaces (eg, the hydrophobic polystyrene surface used in routine ELISA for RFs), or under certain physico‐chemical conditions (eg, elevated temperature) 9 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the presence of residual moisture, freeze‐dried proteins can undergo disulfide interchange and other reactions 13 . Therefore, the data we obtained on the specificity of RF detected in the blood of rheumatoid arthritis patients are consistent with the data that the pathological RF is specific to epitopes that are hidden in the IgG structure (cryptic epitopes) and only become exposed by conformational changes, which may occur upon antigen binding in vivo or in vitro, upon immobilization on surfaces (eg, the hydrophobic polystyrene surface used in routine ELISA for RFs), or under certain physico‐chemical conditions (eg, elevated temperature) 9 …”
Section: Discussionsupporting
confidence: 84%
“…13 Therefore, the data we obtained on the specificity of RF detected in the blood of rheumatoid arthritis patients are consistent with the data that the pathological RF is specific to epitopes that are hidden in the IgG structure (cryptic epitopes) and only become exposed by conformational changes, which may occur upon antigen binding in vivo or in vitro, upon immobilization on surfaces (eg, the hydrophobic polystyrene surface used in routine ELISA for RFs), or under certain physico-chemical conditions (eg, elevated temperature). 9 Thus, the regulatory rheumatoid factor detected in the blood of healthy donors by agglutination of tanned IgG-loaded erythrocytes and the pathology-associated rheumatoid factor detected by latex fixation differ in their specificity.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray structures of Abs have mainly been limited to isolated Fab and Fc parts, even though a few structures of whole Abs have been published [60,61]. However, recent results using ion exchange-purified IgGs and chemical cross-linking in combination with MS have shown that native IgGs have a compact ("closed") structure [62].…”
Section: Discoverymentioning
confidence: 99%
“…45,46 Besides, recent evidence indicates that RFs recognize cryptic epitopes on the Fc fragment, different for IgM's or IgA's, that seem exposed only after a conformational change of the IgG induced upon antigen binding. 47 This may somewhat afford an explanation to why only RF isotype IgA correlated with P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%